Measuring Market Trust: The Impact of Audit Timeliness and Auditor Reputation on Investor Reaction - Valenstya, Devita; Ricky, Ricky (Journal of Business and Economics Research (JBE), 2025)
This study aims to examine the effect of audit delay, auditor reputation, and market value on investor reaction in companies listed in the Kompas 100 index. The research sample consists of 96 observations obtained through purposive sampling during the period 2022 to 2024. Data were analyzed using panel regression to assess the influence of each independent variable on investor reaction. The findings reveal that audit delay has no significant effect on investor reaction, with an effect value of 0.01 and a significance level of 0.993. Similarly, market value does not affect investor reaction, with an effect value of 0.67 and a significance level of 0.505. In this study, market value refers to market capitalization, and the lack of significant effect can be explained by the fact that the companies included in the Kompas 100 index tend to have relatively stable capitalization, making it less of a key factor in short-term investment decision-making. In contrast, auditor reputation has a positive and significant effect on investor reaction, with an effect value of 2.71 and a significance level of 0.008, indicating that auditor quality is an important consideration for investors in making investment decisions. These results emphasize the crucial role of reputable auditors in maintaining market confidence and providing positive signals regarding corporate performance and transparency.